The mouse and his child - Hoban, Russell; Small, David, 1945- (New York : Arthur A. Levine Books, 2001)
Two discarded toy mice survive perilous adventures in a hostile world before finding security and happiness with old friends and new.
Keywords: Toys -- Fiction; Mice -- Fiction; Families -- Fiction; Dollhouses -- Fiction; Animals -- Fiction